2011
DOI: 10.1007/s10646-011-0836-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl

Abstract: The physiological responses and Cu accumulation of Paulownia fortunei (Seem) Hemsl. were studied under 15.7-157 μmol L(-1) Cu treatments in liquid culture for 14 days; the impacts of Cu concentration in the seedlings were evaluated under Cu mine tailing culture with acetic acid and EDTA treatment for 60 days. Results showed that the concentrations of Chl-a, Chl-b and Carotenoids significantly increased (p < 0.05) at 15.7-78.7 μmol L(-1)Cu treatment and significantly decreased at 157 μmol L(-1) treatment after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…The exception was Cu, which reached concentrations above the normal value of 20 mg kg -1 , even in the non-contaminated soil (maximum value of 120 mg kg -1 in V soil). The ability of this species to accumulate Cu has been previously reported by other authors (Jiang et al, 2012).…”
Section: Plant Chemical Compositionsupporting
confidence: 80%
See 1 more Smart Citation
“…The exception was Cu, which reached concentrations above the normal value of 20 mg kg -1 , even in the non-contaminated soil (maximum value of 120 mg kg -1 in V soil). The ability of this species to accumulate Cu has been previously reported by other authors (Jiang et al, 2012).…”
Section: Plant Chemical Compositionsupporting
confidence: 80%
“…Recent studies have shown that some Paulownia species show a relatively high tolerance to the presence of high concentrations of trace elements in the soil (Jiang et al, 2012;Madejón et al, 2014). Species in the Paulownia genus are highly adaptive to a wide range of climate and soil conditions (Yadav et al, 2013), and their use has been proposed for the afforestation of semi-arid areas, given their relatively good performance even under low water irrigation regimens (García-Morote et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects of copper treatments on soluble sugar contents were reported by other authors (Jiang et al 2012) but the effect of copper was very significantly enhanced by EDTA in our system. Higher soluble sugar levels can be detected after 0.1 mM CuCl 2 + 300 mM EDTA treatments in the stem which is the most important plant part in the agricultural and industrial practice.…”
Section: Effect Of Edta- Copper-and Combined Treatments On Biomass Psupporting
confidence: 93%
“…Sample collection and treatment were based on the method of Jiang et al (2012). The physicochemical properties of Pb tailings were as follow: available P 8.46 mg kg À1 , available K 23.27 mg kg À1 , available N 5.075 mg kg À1 , pH (CaCl 2 ) 6.23, and Pb 706.93 mg kg À1 .…”
Section: Physicochemical Properties Of Pb Tailings and Seedling Cultimentioning
confidence: 99%